Thunderstorm asthma: a review, risks for Aotearoa New Zealand, and health emergency management considerations - Stewart C; Young NL; Kim ND; Johnston DM; Turner R (New Zealand Medical Association, 2022)
AIM: To provide an up-to-date review of thunderstorm asthma (TA), identifying causative factors, and to discuss implications for management of TA in New Zealand. METHODS: A literature search was carried out to identify articles that investigate the characteristics and causative factors of TA. Nine electronic databases were searched, yielding 372 articles, reduced to 30 articles after screening for duplication and relevance. RESULTS: TA is globally rare, with 29 reported events since 1983, but is expected to increase in frequency as Earth warms. Triggers include both pollen (particularly ryegrass pollen) and fungal spores. Individual risk factors include outdoor exposure, sensitivity to triggering allergens and history of seasonal allergic rhinitis. History of asthma is not a strong risk factor but is associated with severity of outcome. Limited data on demographic characteristics suggests that individuals aged between 20 and 60 and (in Australasia) of Asian/Indian ethnicity are at higher risk. A single TA event has been reported in New Zealand to date, but much of New Zealand may be at risk of future events given that ryegrass pastures are widely distributed, and summer thunderstorms can occur anywhere. CONCLUSIONS: We recommend developing rapidly deployable public messaging to support the health emergency management response to future TA events, together with the instigation of routine aeroallergen monitoring.
Copyright and source must be acknowledged
Keywords: Adult; Allergens; Asthma; Humans; Middle Aged; New Zealand; Pollen; Rhinitis, Allergic, Seasonal; Young Adult; 11 Medical and Health Sciences